APPLICATION OF MULTI-AGENT SYSTEMS IN SCIENTIFIC RESEARCH - Tsymbal, A.S. (Sworld-Us Conference proceedings, 2025)
The paper examines modern multi-agent systems, particularly those integrating large language models such as CrewAI. It demonstrates that such systems are capable of supporting the research process by facilitating information collection, source analysis, a